2006
DOI: 10.21273/hortsci.41.5.1206
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Application Method Affects Growth, Nutrient, and Water Use Efficiency of Container-Grown Shade Tree Whips

Abstract: The mineral nutrition requirements and fertilizer application methods for container-grown shade tree whips are not well understood. This experiment was conducted to determine the effects of fertility method (water soluble vs. controlled release) on growth, water, and N use efficiency of four taxa [(Acer ×freemanii `Jeffersred' (Autumn Blaze® maple), Cercis canadensis L. (Eastern redbud), Malus (Mill.), `Prairifire' (Prairi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…For 20VC + NPK, 20VC + NK, 20VC + N, and PBS + NPK, the NUE N was 12%, 11%, 15%, and 9% and NUE P was 8%, 11%, 12%, and 7%, respectively (Tables 4 and 5). These nutrient use efficiency values are at the lower end of the ranges reported by others (Owen et al, 2008;Ristvey et al, 2007;Stoven et al, 2006). For azalea (Rhododendron var.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…For 20VC + NPK, 20VC + NK, 20VC + N, and PBS + NPK, the NUE N was 12%, 11%, 15%, and 9% and NUE P was 8%, 11%, 12%, and 7%, respectively (Tables 4 and 5). These nutrient use efficiency values are at the lower end of the ranges reported by others (Owen et al, 2008;Ristvey et al, 2007;Stoven et al, 2006). For azalea (Rhododendron var.…”
Section: Resultsmentioning
confidence: 48%
“…Specific crop nutrient requirements will also influence nutrient use efficiencies. Stoven et al (2006) reported NUE N of 6%, 14%, 36%, and 55% for Quercus rubra L. (red oak), Malus (Mill.) 'Prairifire' (Prairifire crabapple), Cercis canadensis L. (Eastern redbud), and Acer ·freemai 'Jeffersred' (Autumn Blaze Ò maple), respectively, when grown outdoors and fertilized with CRF.…”
Section: Resultsmentioning
confidence: 99%
“…Sufficient basal fertilizer should be put in place before planting. Two months after planting, according to the nutrient requirement of the tree, it should be judged whether to apply additional compound fertilizers to the seedlings to promote the robust and healthy formation of the trees (Milosevic et al, 2019;Rose, 1999;Rose et al, 1999;Stoven et al, 2006). According to the nutrient demand of fruit trees and the environmental benefit characteristics of fertilization at this stage, we can judge whether to add compound fertilizer with different components before or after flowering to promote the normal development of flowers and fruit (Ge et al, 2017;Neilsen et al, 2001).…”
Section: Cultivationmentioning
confidence: 99%
“…However, the gradual release of nutrients from the growth media necessitates the use of fertilization to improve plant growth and strengthen resistance to biotic and abiotic stresses. Fertilization is an important measure in seedling cultivation, which can promote seedling growth, soil fertility, and seedling quality [10]. At present, numerous scholars have begun to pay attention to the study of C. camphora seedlings, mainly from the aspects of landscaping [1,11], gene identification [12,13], pest control [7] and other aspects.…”
Section: Introductionmentioning
confidence: 99%